FINANCIAL FEASIBILITY ANALYSIS OF ORGANIC VEGETABLE FARMING AT CV. RAHAYU IN VILLAGE OF SIDERA SUB-DISTRICT OF SIGI BIROMARU REGENCY OF SIGI - Ferdison S. Mantende; Marhawati Mapatoba; Abdul Muis (Tadulako University, 2017)
This research aimed to analyze the financial feasibility of organic vegetable farming at CV. Rahayu. This research conducted in Sidera, Subdistrict of Sigi Biromaru, Regency of Sigi on December 2016 to January 2017. The respondents were purposively determined. Data was analyzed using financial worthiness analysis employing with 4 indicators: Net present value (NPV), net benefit cost ratio (Net B/C), internal rate of return (IRR), and Payback Period (PP). The results of this research indicated that the NPV during the period 2014 to 2018 was IDR 543.674.792; the net B/Cwas 1,65, the IRR was 35,09 %, and the PP was 2 years and 3 months. The results of the calculationusing sensitivity analysis in the organic vegetable farming company at CV. Rahayu by assuming the organic vegetables attacked by the pests and diseases were a decreased 33 percent from total production with the acquisition of NPV decreased to IDR 8.587.415, Net B/C decreased to 1.01, IRR decreased to 12.42 percent, Payback period became 3.6 years. In the other hand, NPV decreased to IDR 7,276,181, Net B/C decreased to 1.01, IRR decreased to 12.36 percent, payback period became 3.6 years if the assume was an increased production cost until 74 percent. These values financially show the farming at CV. Rahayu is well worth to effort. These results indicate that financially, CV. Rahayu is very feasible to operate.